Remodeling of liver phospholipidomic profile in streptozotocin-induced diabetic rats - Simoes, Claudia
Lipid homeostasis in liver is known to be altered with diabetes mellitus, ultimately leading to liver damage and related complications. The present work aimed to evaluate changes in the liver phospholipid profile after 4 months of uncontrolled hyperglycemia. Twenty Wistar rats were divided into two groups: control and streptozotocin-treated (T1DM). After 4 months, animals were sacrificed and morphological characterization of liver was performed and related with serum markers of hepatic damage. Lipid extracts were obtained from liver and phospholipid (PL) classes were quantified. Lipid molecular species were determined by LC-MS and LC-MS/MS, and fatty acids by GC-MS. Concomitantly with signs of hepatic damage we found variations in the relative amount of phospholipid classes in T1DM, characterized by a decrease in PLs with choline head group, and by an increase in the relative content of other PL classes. A remodeling in PL fatty acyl chains was observed in T1DM liver, with a similar pattern to all the PL classes, and consisting in the reduction of 16:0 and an increase of 18:0 and 18:2 acyl chains. The observed changes in T1DM lipid profile may contribute to the altered membrane properties underlying hepatic damage, worsening the metabolic alterations that characterize T1DM. (c) 2013 Elsevier Inc. All rights reserved.